Electricity Access and Structural Transformation : Evidence from Brazil's Electrification - Perez-Sebastian, Fidel (World Bank, Washington, DC, 2020)
This study proposes a novel supply-side mechanism driving economic structural transformation: grid electrification. Increasing electricity availability affects the reallocation of inputs to more productive activities through generating higher returns and lowering entry costs in sectors with greater infrastructure intensity. The results of modeling and econometric analysis based on Brazil's historical data over the period 1970-2006 confirm that the manufacturing sector benefits the most in these two dimensions, followed by services and agriculture. The expansion of electricity infrastructure explains about 17 percent of this process and 32 percent of the observed increase in GDP per capita. Simulations of a multisector neoclassical growth model with heterogeneous firms help assessing the effectiveness of different electrification policies.